Global warming potential and its cost of mitigation from maize (Zea mays) - wheat (Triticum aestivum) cropping system - FAGODIYA, R K; PATHAK, H; BHATIA, A; JAIN, N; GUPTA, D K (The Indian Journal of Agricultural Sciences, 2020)
The maize (Zea mays L.) - wheat (Triticum aestivum L.) cropping system (MWCS) could be better alternative to rice-wheat cropping system (RWCS), due to its lower water requirement, methane (CH4) emission and soil degradation. However, the global warming potential (GWP), greenhouse gas intensity (GHGi) and benefit cost ratio (BCR) of the MWCS need to be quantified in order to propose management practices for GWP mitigation. To achieve the objective of the study a field experiment was conducted at the ICAR-IARI, New Delhi during 2012-14. The experiment consisted of six treatments, viz. N0 (control), Urea, Urea+FYM, FYM, Urea+NI (nitrification inhibitor) and NOCU (neem oil coated urea). Two-year average results showed that as compared to urea treatment, GWP of MWCS lowered by 6, 16, 31 and 62% in urea+NI, NOCU, Urea+FYM and FYM, respectively. GHGi lowered by 6, 6, 24 and 46% in urea+NI, NOCU, Urea+FYM and FYM, respectively. The BCR was higher in NOCU and Urea+NI as compared to urea treatment; however, it was lower in FYM and urea+FYM. Thus, NOCU is capable for mitigating GWP and lowering GHGi with higher BCR from MWCS.